ARCHAEOLOGICAL AREA MAYORAZGO / PURUCHUCO-HUAQUERONES: THE CULTURAL HERITAGE IN SALMUERA - Bueno Mendoza, Alberto (2014)
Information concerning the destruction of a major Andean archaeological site by the Peruvian State is presented. The archaeological heritage is being gradually destroyed in recent decades resulting from the expansion of urbanization, agricultural land and civil works.